Economic Evaluation of Cobalt Ferrite (CoFe2O4) Nanoparticles Using Thermal Decomposition Synthesis Method - Sadina Sahitya Dewi; Wafa Raihanah Arwa; Dewi Yulina Nur Soleha; Silmi Ridwan Putri; Asep Bayu Dani Nandiyanto (Urecol Journal. Part E: Engineering, 2021)
The purpose of this study was to determine the technical and economic feasibility of a project to manufacture CoFe2O4 nanoparticles using the thermal decomposition synthesis method on an industrial scale. The method used in economic evaluation is to compare several parameters such as gross profile margin (GPM), payback period (PBP), breakeven points (BEP), internal rate return (IRR), cumulative net present value (CNPV), return on investment (ROI), and profitability index (PI). The results show that the production of CoFe2O4 nanoparticles is profitable on an industrial scale with a relatively lower selling price than the market price and a relatively small size. This project can run within nine years and the investment will be profitable within 2 years according to PBP results.